2017
DOI: 10.3389/fpls.2017.01194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Root Diameter and Soil Depth on the Xylem Anatomy of Fine- to Medium-Sized Roots of Mature Beech Trees in the Top- and Subsoil

Abstract: Despite their importance for water uptake and transport, the xylem anatomical and hydraulic properties of tree roots have only rarely been studied in the field. We measured mean vessel diameter (D), vessel density (VD), relative vessel lumen area (lumen area per xylem area) and derived potential hydraulic conductivity (Kp) in the xylem of 197 fine- to medium-diameter roots (1–10 mm) in the topsoil and subsoil (0–200 cm) of a mature European beech forest on sandy soil for examining the influence of root diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 79 publications
(142 reference statements)
3
29
0
Order By: Relevance
“…Increased vessel lumen diameter with cambial age was in line with previous below- [63] and aboveground studies [12,28,64]. Increased early-and latewood vessel lumen diameter, as well as increased vessel element length with cambial age, improves water transport efficiency.…”
Section: Vertical and Radial Patterns Of Wood Anatomical Traitssupporting
confidence: 89%
“…Increased vessel lumen diameter with cambial age was in line with previous below- [63] and aboveground studies [12,28,64]. Increased early-and latewood vessel lumen diameter, as well as increased vessel element length with cambial age, improves water transport efficiency.…”
Section: Vertical and Radial Patterns Of Wood Anatomical Traitssupporting
confidence: 89%
“…Indeed, the fine root morphology, anatomy and water flow resistance do vary with depth in woody species (McElrone et al 2004;Wang et al 2015). However, no such information is available for sycamore maple, and the xylem anatomical and hydraulic properties of beech fine roots were not significantly influenced by soil depth in the study conducted by Kirfel et al (2017). Studies focusing on water Fig.…”
Section: Shallow Water Uptake By Treesmentioning
confidence: 94%
“…The calculated GOC contribution for Miocene sand was comparatively low (29 %-77 %) compared with the contribution for Red Sandstone and loess, especially at 5 m depth. Compared with the Red Sandstone, this could be due to deep biogenic carbon inputs, such as roots and root exudates from the trees John et al, 2016;Kirfel et al, 2017;Tückmantel et al, 2017), since the loosely bedded Miocene sand allows for deep infiltration compared with the Red Sandstone site with its shallow bedrock as a root-restricting layer (Schneider and Don, 2019). Although it was not possible to define the exact rooting depth for Miocene sand, this depth probably does not exceed 4 m, according to Schenk and Jackson (2005).…”
Section: Site-dependent Contents Of Gocmentioning
confidence: 99%
“…This type of carbon is considered a highly stable carbon pool due to its apparently high 14 C ages (Mathieu et al, 2015;Schrumpf et al, 2013). However, another explanation for this could be the contribution of geogenic organic carbon (GOC), which is defined here as OC that originates from deposition during sedimentation and rock formation and may increasingly influence subsoil OC with depth (Graz et al, 2010;Kögel-Knabner et al, 2008;Schrumpf et al, 2013;Trumbore, 2009). GOC, in most cases, is devoid of 14 C and, thus, may lead to an overestimation of ancient OC sources, although a number of studies showed the importance of root-derived young OC inputs to subsoils (Angst et al, 2016;Crow et al, 2009).…”
Section: Introductionmentioning
confidence: 99%